Comparative Transcriptome and Proteome Analysis Provides New Insights Into the Mechanism of Protein Synthesis in Kenaf (Hibiscus cannabinus L.) Leaves - Zhang, Chao; Deng, Yong; Zhang, Gaoyang; Li, Jianjun; Xiao, Aiping; Zhao, Lining; Chen, Anguo; Tang, Huijuan; Chang, Li; Pan, Gen; Wu, Yingbao; Zhang, Jiangjiang; et al. (Frontiers in Plant Science, 2022)
Given the rising domestic demand and increasing global prices of corn and soybean, China is looking for alternatives for these imports to produce animal fodder. Kenaf (Hibiscus cannzzbinus L.) has great potential as a new forage source, due to abundant proteins, phenols and flavonoids in its leaves. But few studies have evaluated the mechanism of protein synthesis in kenaf leaves. In the current work, by determine the crude protein content in the leaves of two kenaf materials, it was determined that the protein content of the kenaf material "Q303" leaves was higher; combined with transcriptome and proteome data, the kenaf samples were systematically studied to obtain mRNA-protein correlation. Then, the genes/proteins related to protein synthesis in the kenaf leaves were obtained. Moreover, this work detected mRNA expression of 20 differentially expressed genes (DEGs). Meanwhile, 20 differentially expressed proteins (DEPs) related to protein synthesis were performed parallel reaction monitoring. Fructose-1,6-bisphosphotase (FBP), nitite reductase (NirA), prolyl tRNA synthase (PARS) and glycine dehydrogenase (GLDC) presented increased mRNA and protein levels within kenaf leaves with high protein content. Based on the obtained findings, FBP, NirA, PARS and GLDC may exert a vital function in the protein synthesis of kenaf leaves. The results provide a new idea for further studying the potential genes affecting the quality trait of protein content in kenaf leaves and provide gene resources and a theoretical foundation for further cultivating high protein kenaf varieties.